Complex Light and Optical Forces VII 2013
DOI: 10.1117/12.2000544
|View full text |Cite
|
Sign up to set email alerts
|

MEMS axicons for nondiffracting line shaping of ultrashort pulses

Abstract: For a growing number of applications in nonlinear spectroscopy, micro-and nano-machining, optical data processing, metrology or medicine, an adaptive shaping of ultrashort pulsed, ultrabroadband laser beams into propagation-invariant linear focal zones is required. One example is the femtosecond laser high-speed large area nanostructuring with moving substrates and cylindrical optics we reported about recently. Classical microoptical systems, however, distort the temporal pulse structure of few cycle pulses by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The obtaineded FWHM time duration of the autocorrelation function in (a,c) is unrealistically short because of a spatial cut due to incomplete spatial superposition. Incontrast, the spatial superposition in (b,d) is nearly complete and delivers a pulse duration close to the value expected by reference measurements with spectral phase interferometry by direct electric-field reconstruction (SPIDER) [9]. The corresponding pulse duration for the used configuration was found to be about 8 fs.…”
Section: Fresnel Bi-mirrorsmentioning
confidence: 59%
See 2 more Smart Citations
“…The obtaineded FWHM time duration of the autocorrelation function in (a,c) is unrealistically short because of a spatial cut due to incomplete spatial superposition. Incontrast, the spatial superposition in (b,d) is nearly complete and delivers a pulse duration close to the value expected by reference measurements with spectral phase interferometry by direct electric-field reconstruction (SPIDER) [9]. The corresponding pulse duration for the used configuration was found to be about 8 fs.…”
Section: Fresnel Bi-mirrorsmentioning
confidence: 59%
“…By the superposition of both partial beams, this leads to the formation of "light blades" -extended (quasi-nondiffracting) linear focal zones [9]. Their number, thickness and length can be tuned by adjusting the tilt angle of the mirrors.…”
Section: Fresnel Bi-mirrorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresnel mirrors can, for example, be used to fabricate linear optical gratings directly into the photoresist without the use of a photomask [3]. It was shown that an adaptive Fresnel mirror can be used in adaptive pulse autocorrelation [4], and for direct nano-machining of subwavelength structures on silicon or dielectric substrates by laser-induced periodic surface structures (LIPSS) [5,6]. LIPSS are formed by the interference of incident and scattered light pulses on the surface of the material [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed the use of an adaptive Fresnel mirror for direct nanomachining of sub-wavelength structures into silicon or dielectric substrates by laser-induced periodic surface structures (LIPSS), generated by femtosecond laser pulses [9][10][11]. In this application, the Fresnel mirror is intended to deliver a sharp line pattern, while introducing only a minimal amount of optical dispersion into the system.…”
Section: Introductionmentioning
confidence: 99%